Sexual satisfaction among patients with erectile dysfunction on oral phosphodiesterase inhibitors and among patients with penile prosthetic implants. Issue 2 (June 2016) - Mostafa, Rashad M.; NasrAlla, Yasser S.; Alakhras, Atef I.; Al-Hitaree, Khalid A.
Abstract : Introduction: Erectile dysfunction (ED) is a global problem, and although oral phosphodiesterase-5 (PDE-5) inhibitor drugs have revolutionized the treatment of ED, there still are many cases who fail to respond to these drugs or who present with other pathologies that need the penile prosthetic implant (PPI) surgery. Purpose: The aim of the present study was to assess sexual satisfaction in ED patients on penile prosthesis and on oral PDE-5 inhibitors. Materials and methods: This comparative, cross-sectional study included two groups of ED patients recruited from the Andrology Outpatient Clinic of Suez Canal University Hospital, Ismailia, Egypt: group 1, in which patients were treated with penile prosthesis implantation (29), and group 2, which included patients on PDE-5 inhibitors treatment (35). Patients were asked to answer a validated questionnaire (Erectile Dysfunction Inventory of Treatment Satisfaction). Results: The overall score of treatment satisfaction was significantly higher in the group treated with penile prosthesis surgery than that in the group treated with oral drugs: 93.55±7.34 versus 75.06±17.22. Libido and the frequency of intercourse increased with PPI. Conclusion: PPI surgery is a valid and successful way of treating ED patients; it provides patients with a higher satisfaction rate than does oral PDE-5 inhibitor.